Effect of Cold Stress on Neurobehavioral and Physiological Parameters in Rats - El Marzouki, Hajar; Aboussaleh, Youssef; Najimi, Mohamed; Chigr, Fatiha; Ahami, Ahmed (Frontiers in Physiology, 2021)
Cold stress is an important current issue and implementing control strategies to limit its sometimes harmful effects is crucial. Cold is a common stressor that can occur in our work and our occupational or leisure time activities every day. There are substantial studies on the effects of chronic stress on memory and behavior, although, the cognitive changes and anxiety disorders that can occur after exposure to chronic intermittent cold stress are not completely characterized. Therefore, the present study was undertaken with an aim to investigate the effect of this stress on physiological and neurobehavioral parameters using cognitive and behavioral test batteries. We generated a cold stress model by exposing rats to cold (4 ° C, 2h/day) for 5 consecutive days and in order to test for the potential presence of sex differences, a comparable number of male and female rats were tested. The body weight gain, food intake and the adrenal glands weight of each group were measured. Spatial working memory and recognition memory were assessed using the Y maze and the NOR tasks. While, gender differences in the effect of chronic stress on behavior were evaluated by the elevated plus maze (EPM), open field maze (OF), and Marble burying (MB) tests. Our results showed that cold exposure increased body weight and relative adrenal weight in male rats. While females showed decreased food intake with no change in body weight and relative adrenal weight . Both sexes successfully performed the Y maze (YM) and object recognition (OR) tasks, indicating intact spatial working memory performance and object recognition abilities in both male and female rats. In addition, we have shown that stress caused an increase in the level of anxiety in male rats. In contrast, the behavior of the female rats was not affected by cold exposure. In summary, the current results provide preliminary evidence that chronic intermittent cold stress model may not be an efficient stressor to female rats. Females exhibit resilience to cold exposure that causes an increase in the level of anxiety in male rats, which demonstrates that they are affected differently by stress.